1998
DOI: 10.3171/foc.1998.4.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Gait before and 10 years after rhizotomy in children with cerebral palsy spasticity

Abstract: Selective dorsal rhizotomy is a neurosurgical procedure performed for the relief of spasticity in children with cerebral palsy, but its long-term functional efficacy is still unknown. The authors sought to address this issue by means of an objective, prospective study in which quantitative gait analysis was used. Eleven children with spastic diplegia (mean age at initial surgery 7.8 years) were evaluated preoperatively in 1985 and then at 1, 3, and at least 10 years after surgery. For comparison, 12 ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 17 publications
0
38
0
Order By: Relevance
“…16 Clinical studies have demonstrated that SDR results in short-and long-term improvement in lower-extremity tone and can lead to improved mobility, improved lower-limb function, decreased need for orthopedic surgical interventions, and an increased level of self-care for children with spastic diplegia and spastic quadriplegia. 2,5,7,8,10,12,15,18,19 Although nerve rootlet transection is limited to the lumbosacral rootlets in SDR, early anecdotal reports in the 1980s suggested the unexpected observation of improvements above the level of the lower extremities, termed "suprasegmental effects." Over the next decade, a number of small case series emerged describing improvement in upper-extremity function or tone following SDR, but only described qualitative improvement or quantitative improvement in select upper-extremity muscle groups.…”
Section: ©Aans 2013mentioning
confidence: 99%
See 1 more Smart Citation
“…16 Clinical studies have demonstrated that SDR results in short-and long-term improvement in lower-extremity tone and can lead to improved mobility, improved lower-limb function, decreased need for orthopedic surgical interventions, and an increased level of self-care for children with spastic diplegia and spastic quadriplegia. 2,5,7,8,10,12,15,18,19 Although nerve rootlet transection is limited to the lumbosacral rootlets in SDR, early anecdotal reports in the 1980s suggested the unexpected observation of improvements above the level of the lower extremities, termed "suprasegmental effects." Over the next decade, a number of small case series emerged describing improvement in upper-extremity function or tone following SDR, but only described qualitative improvement or quantitative improvement in select upper-extremity muscle groups.…”
Section: ©Aans 2013mentioning
confidence: 99%
“…4 The advancement of intraoperative electrophysiological monitoring allowed for the development and popularization of the selective dorsal rhizotomy (SDR) in the 1980s. 13,14,17,18 Selective dorsal rhizotomy involves a selective transection of lower-extremity sensory nerve rootlets based on EMG data and manual palpation of muscle groups indicating excessive levels of diffuse excitatory input when Ia afferent nerve fibers are stimulated. 16 Clinical studies have demonstrated that SDR results in short-and long-term improvement in lower-extremity tone and can lead to improved mobility, improved lower-limb function, decreased need for orthopedic surgical interventions, and an increased level of self-care for children with spastic diplegia and spastic quadriplegia.…”
Section: ©Aans 2013mentioning
confidence: 99%
“…4,7,9,18 Three randomized controlled trials and other nonrandomized prospective studies have provided strong evidence that SDR decreases lower-extremity spasticity in children with spastic diplegia. 4,17 Additional studies have demonstrated maintenance of the postoperative benefits in the long term.…”
Section: Selective Dorsal Rhizotomymentioning
confidence: 99%
“…In a 1998 review, Subramanian, et al, 17 showed with moderate certainty that the rate of orthopedic surgery after SDR is approximately 65%. In our three studies, we only found such high rates of orthopedic surgery in children with quadriplegia who underwent SDR at an older age (6-14 years) and who all needed assistance walking at follow-up evaluation.…”
Section: Frequency Of Orthopedic Surgery Post-sdr Is Not As High As Pmentioning
confidence: 99%